Transcriptional reprogramming at the intersection of the heat shock response and proteostasis - Pessa, Jenny C. (United States, 2025)
Cellular homeostasis is constantly challenged by a myriad of extrinsic and intrinsic stressors. To mitigate the stress-induced damage, cells activate transient survival programs. The heat shock response (HSR) is an evolutionarily well-conserved survival program that is activated in response to proteotoxic stress. The HSR encompasses a dual regulation of transcription, characterized by rapid activation of genes encoding molecular chaperones and concomitant global attenuation of non-chaperone genes. Recent genome-wide approaches have delineated the molecular depth of stress-induced transcriptional reprogramming. The dramatic rewiring of gene and enhancer networks is driven by key transcription factors, including heat shock factors (HSFs), that together with chromatin-modifying enzymes remodel the 3D chromatin architecture, determining the selection of either gene activation or repression. Here, we highlight the current advancements of molecular mechanisms driving transcriptional reprogramming during acute heat stress. We also discuss the emerging implications of HSF-mediated stress signaling in the context of physiological and pathological conditions.